2021
DOI: 10.1097/md.0000000000027677
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of poor glycemic control among type 2 diabetes mellitus patients treated with antidiabetic medications

Abstract: This study aimed to clarify of the predictors of poor glycemic control in type 2 diabetes mellitus (T2DM) patients treated with antidiabetic medications in China.This study was a retrospective, cross-sectional study based on SuValue database. T2DM patients aged 18 years or older performing glycosylated hemoglobin A1c (HbA1c) examinations from January 1st, 2018 to December 31st, 2018 were included and have been treated with antidiabetic medications for at least 6 months. HbA1c < 7.0% was defined as adequate gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…Evidence has shown that longer diabetes duration is associated with poor glucose control (Alzaheb and Altemani, 2018;Chetoui et al, 2019;Demoz et al, 2019;Fiseha et al, 2018;Wang et al, 2021), a finding we also observed in our study. Our study also found that better fasting blood glucose was recorded amongst those with shorter diabetes duration (< 2 years).…”
Section: Discussionsupporting
confidence: 91%
“…Evidence has shown that longer diabetes duration is associated with poor glucose control (Alzaheb and Altemani, 2018;Chetoui et al, 2019;Demoz et al, 2019;Fiseha et al, 2018;Wang et al, 2021), a finding we also observed in our study. Our study also found that better fasting blood glucose was recorded amongst those with shorter diabetes duration (< 2 years).…”
Section: Discussionsupporting
confidence: 91%
“…Related research shows that residents in economically underdeveloped areas have a higher incidence of DFU [ 31 ]. Kashi Prefecture, where the patients enrolled in our study came from, is a border city in northwestern China and represents an undeveloped and poorly resourced area.…”
Section: Discussionmentioning
confidence: 99%
“…As the duration of diabetes increases, glycaemic control worsens which has also been shown in our study. [3,20,22,[28][29][30] Similarly, in the majority of relevant studies it has been reported that a longer diabetes duration was related to poor glycaemic control. [3,4,27,[30][31][32] In contrast, in another study evaluating the risk factors related to poor glycaemic control reported that 81.0% of patients with poor glycaemic control had a diabetes duration of <7 years.…”
Section: Discussionmentioning
confidence: 99%